2019
DOI: 10.1590/s1980-220x2017047603432
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between quality of life and burden of family caregivers of infants with cleft lip and palate

Abstract: Objective: To evaluate the correlation between measures of quality of life and burden in family caregivers of infants with cleft lip and palate and to analyze possible associations between quality of life and sociodemographic variables. Method: Exploratory, cross-sectional study conducted in hospital specialized in the treatment of craniofacial anomalies, with caregivers who answered the following data collection instruments: sociodemographic characterization form, World Health Organization Quality of Life - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 23 publications
0
13
0
4
Order By: Relevance
“…Beluci et al reported that caregivers with greater burdens have a worse perception of the quality of life. They also described that the perception of rehabilitation and the coping capacity of CLP children are influenced by the expectations, attitudes and support of their parents [ 20 ]. Difference on OHRQoL scores by children and their parents were reported with parents underestimate the “Oral symptoms” but overestimate “Functional Well-Being” of having a cleft [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beluci et al reported that caregivers with greater burdens have a worse perception of the quality of life. They also described that the perception of rehabilitation and the coping capacity of CLP children are influenced by the expectations, attitudes and support of their parents [ 20 ]. Difference on OHRQoL scores by children and their parents were reported with parents underestimate the “Oral symptoms” but overestimate “Functional Well-Being” of having a cleft [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the health care modalities provided by informal caregivers, there are the support for the development of daily life activities, in addition to financial, psychological, and spiritual assistance (4) . The experience of being the main care provider can be a burden for the caregiver, leading to adaptations and deprivations that, in many cases, lead to overload, depressive symptoms, anxiety, increased stress levels, and a worse perception of the quality of life (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%
“…Geralmente, a gestante idealiza um bebê esteticamente e funcionalmente perfeito. Ideal esse que pode ser rompido quando os pais se confrontam com um dos maiores temores de uma gestação: o diagnóstico de uma malformação (Beluci, Dantas, Mondini, & Trettene, 2019;Cunha et al, 2019;Dadalto, Cunha, & Monteiro, 2019;Oliveira, 2017).…”
Section: Introductionunclassified